The relationship between oral diseases and infectious complications in patients under dialysis. (19th February 2020) - Arenius, Ilona; Ruokonen, Hellevi; Ortiz, Fernanda; Furuholm, Jussi; Välimaa, Hannamari; Bostanci, Nagihan; Eskola, Maija; Maria Heikkinen, Anna; Meurman, Jukka H.; Sorsa, Timo; Nylund, Karita
Abstract: Objectives: Association was investigated between oral health before dialysis and the incidence of systemic infections during dialysis. We hypothesized that low‐grade systemic inflammation caused by poor oral health associates with infectious episodes in patients on dialysis, despite earlier eradication of oral infection foci. Subjects and methods: A total of 117 patients (46 with peritoneal and 71 with hemodialysis) were examined and treated at predialysis stage and followed up during dialysis. Number of infection episodes and microorganisms cultured from blood and peritoneal fluid were analyzed. Number of teeth, periodontal inflammatory burden, and total dental index scores were assessed, and salivary matrix metalloproteinase 8, triggering receptor on myeloid cells 1, peptidoglycan recognition protein 1 (PGLYRP1), and interleukin‐1β were measured. Results: In hemodialysis, 134 infection episodes were recorded, while peritoneal dialysis group had 77 peritonitis episodes. Culture‐negative samples were 69% in hemodialysis and 23% in peritoneal dialysis group. Staphylococci were the most frequently associated microorganisms. Infections during dialysis did neither associate with oral health parameters nor associate with salivary inflammatory biomarkers, except for PGLYRP1, which associated with number of infection episodes during hemodialysis ( p  = .046). Conclusions: A number of infection episodes during hemodialysis were associated with salivary PGLYRP1 but not the other salivary markers or oral infection markers.